PENGARUH SALINITAS DAN INOKULAN BAKTERI TERHADAP PERTUMBUHAN TANAMAN TERUNG (Solanum melongena L.) - Suliasih Suliasih; Sri Widawati (BERITA BIOLOGI, 2016)
Nitrogen fixing dan phosphate solubilizing bacteria are important PGPR bacterial in addition of plant nutrients by increasing N and P, especially in saline soils. Experiments were conducted to observe the effects of  soil salinity and bacterial inoculant on growth eggplant (Solanum melongena) at green house of  Microbiology division, Research Center for Biology, The Indonesian Institute of Sciences,  Cibinong. Experiment laid out as factorial based randomized complete design  with three replications. Five levels of watering consisted of (1). Fresh water, (2). NaCl 0.1%, (3). NaCl 1%, (4). Sea water 75 %+25% fresh water, (5). Sea water 100%  as first factors. Five levels of inoculations/biofertilizers consisted of (1).control without fertilizer (K), (2). NPK (P), (3). Nitrogen Fixing bacteria (BPN1), all treatments was repeated 3 times  BPN2, mixed inoculation (BPN1 +  BPN2 + Phosphate Solubilizing Bacteria/BPF) as second factors.  Results showed that biofertilizer application increased growth and yield of eggplant in various levels of salinity at about 21.56%-53.35%  compared to uninoculated plants